STUDI SURVEI PELAKSANAAN ASESMEN PRAKTIKUM DAN KEMAMPUAN INKUIRI MAHASISWA CALON GURU BIOLOGI - Aa Juhanda; Nuryani Y Rustaman; Topik Hidayat; Ana Ratna Wulan (BIO EDUCATIO : (The Journal of Science and Biology Education), 2021)
This survey research is to determine the profile of the implementation of the practicum assessment carried out and the ability of inquiry of prospective Biology teacher students. The subjects of this study were 19 biology education students class 2017/2018 in semester 3 at UMMI who contracted the Invertebrate Zoology practicum course. The instruments used include observation sheets, questionnaires and interviews. Data analysis was performed through descriptive analysis using percentage techniques. The results showed that the implementation of the practicum assessment included: 1) the assessment carried out in the form of performance appraisals and pre-lab quizzes, summative tests 2) practicum learning that was carried out tended to be subjective in nature, which was a cook book; 3) assignments given in the practicum in the form of making journals and practicum reports. In addition, almost all of the students' inquiry abilities could be accessed in the practical assessment but it was not optimal.